Ladies-in-Waiting and Portraiture at Philip II’s Court: Portraits of the Habsburgs and of “Unknown Lady” in the Museo del Prado - Vanessa De Cruz Medina (Boletín del Museo del Prado)
This article focuses on ladies-in-waiting and portraiture at Philip II’s court and provides further information about four portraits in the collection of the Museo del Prado. It explores two understudied areas of women and portraiture such as agency and reception through the private correspondence of Margarita de Cardona and her daughters, ladies-in-waiting to Habsburg women. Their letters show how ladies-in-waiting were portrayed inside the royal palace, how they self-fashioned, the portraits they saw and their thoughts about them. The letters also reveal how some of them learned to paint in order to portray other ladies-in-waiting as well as themselves.